An Explorative Qualitative Study on Pharmacist Active Engagement Approach in Primary Healthcare Diabetic Education - Selvadurai, Selvakumari; Makmor-Bakry, Mohd; Mhd Ali, Adliah (Indonesian Journal of Pharmacy, 2020)
The conventional counseling method focuses on imparting knowledge meanwhile active engagement approach would enhance patient’s participation and control in the health management process. This study explored the various elements that affect the pharmacist-patient active engagement during diabetes counseling sessions in primary healthcare settings. A qualitative study using thematic analysis of semi-structured interviews was utilized. Subjects were recruited from five primary healthcare clinics in Kuala Lumpur. Ten pharmacists actively running the diabetes medication therapy adherence clinical (DMTAC) counseling and 15 patients who are currently enrolled under the DMTAC program participated in this study. A combination of computer software ATLAS.ti and hand-written methods were used in the mind mapping to assist with the development of the themes. The qualitative analysis identified themes associated with pharmacist active engagement approach include establish rapport (subthemes: introduction and greetings, ice-breaking, background check, attitude, pharmacist motivation), getting information to explore the patient problems (subthemes: giving attention, communication, the time factor, re-assess patients’ understanding), building relationship (subthemes: sharing of ideas, emotions, relationship, trust, sensitiveness, support and belief), explanation and planning (subthemes: making a decision and mutual discussion) and closing the session (subthemes: accessibility to pharmacists, DMTAC appointments). This study established areas of active engagement namely, shared decision-making, engaging communication, and motivational interview skills that should be imparted to the pharmacists to enhance the current diabetes counseling practice.